2005
DOI: 10.1016/j.molcel.2005.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Low Histone Ubiquitylation by Ubp10 Correlates with Telomere-Proximal Sir2 Association and Gene Silencing

Abstract: Low levels of histone covalent modifications are associated with gene silencing at telomeres and other regions in the yeast S. cerevisiae. Although the histone deacetylase Sir2 maintains low acetylation, mechanisms responsible for low H2B ubiquitylation and low H3 methylation are unknown. Here, we show that the ubiquitin protease Ubp10 targets H2B for deubiquitylation, helping to localize Sir2 to the telomere. Ubp10 exhibits reciprocal Sir2-dependent preferential localization proximal to telomeres, where Ubp10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
171
3
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(193 citation statements)
references
References 55 publications
14
171
3
5
Order By: Relevance
“…4A, right). This correlation is opposite to the pattern previously observed for H2B ubiquitylation (Emre et al 2005).…”
Section: Sumoylation Is Higher At Subtelomeres Compared With More Intcontrasting
confidence: 99%
“…4A, right). This correlation is opposite to the pattern previously observed for H2B ubiquitylation (Emre et al 2005).…”
Section: Sumoylation Is Higher At Subtelomeres Compared With More Intcontrasting
confidence: 99%
“…2005) and USP7 in humans (Emre et al . 2005). Although histones H3 and H4 have been shown to undergo ubiquitylation, the function of their monoubiquitylated forms is unclear (Cao & Yan 2012), with the exception of H3 monoubiquitylated at K23 by UHRF1 as described below.…”
Section: Histone Monoubiquitylation and Transcriptional Regulationmentioning
confidence: 99%
“…Two deubiquitylating enzymesUbp8 (Henry et al, 2003;Daniel et al, 2004) and Ubp10 (Emre et al, 2005;Gardner et al, 2005)-have been shown to deubiquitylate H2B at K123. The finding that other sites in H2B are ubiquitylated and that K123 can be polyubiquitylated raises the possibility that these noncanonical ubiquitylation events can also be regulated by Ubp8 and/or Ubp10.…”
Section: There Are At Least Two Distinct Types Of Polyubiquitylated H2bmentioning
confidence: 99%
“…Although only ϳ10% of steady-state H2B is monoubiquitylated (Robzyk et al, 2000), it is likely that a much larger percentage of H2B is actually ubiquitylated and that deubiquitylation is an active and crucial process (reviewed in Emre and Berger, 2004). In support of this notion, the H2B-Ub-specific protease Ubp8, which is part of the SAGA complex (Henry et al, 2003;Daniel et al, 2004), is important for gene activation (Henry et al, 2003), whereas Ubp10, which is thought to preferentially remove Ub from H2B at the telomeres (Emre et al, 2005;Gardner et al, 2005), is important for gene silencing (Kahana and Gottschling, 1999). These findings have led to a model in which cycles of H2B ubiquitylation and deubiquitylation provide directionality to different stages in the transcription process (e.g., Wyce et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation